Resting-state connectivity predicts visuo-motor skill learning - Manuel, Aurélie L.; Guggisberg, Adrian G.; Thézé, Raphaël; Turri, Francesco; Schnider, Armin (NeuroImage (Orlando, Fla.), 2018)
Spontaneous brain activity at rest is highly organized even when the brain is not explicitly engaged in a task. Functional connectivity (FC) in the alpha frequency band (α, 8–12 Hz) during rest is associated with improved performance on various cognitive and motor tasks. In this study we explored how FC is associated with visuo-motor skill learning and offline consolidation. We tested two hypotheses by which resting-state FC might achieve its impact on behavior: preparing the brain for an upcoming task or consolidating training gains. Twenty-four healthy participants were assigned to one of two groups: The experimental group (n = 12) performed a computerized mirror-drawing task. The control group (n = 12) performed a similar task but with concordant cursor direction. High-density 156-channel resting-state EEG was recorded before and after learning. Subjects were tested for offline consolidation 24h later. The Experimental group improved during training and showed offline consolidation. Increased α-FC between the left superior parietal cortex and the rest of the brain before training and decreased α-FC in the same region after training predicted learning. Resting-state FC following training did not predict offline consolidation and none of these effects were present in controls. These findings indicate that resting-state alpha-band FC is primarily implicated in providing optimal neural resources for upcoming tasks. •Learning and offline consolidation of mirror-drawing skills are evaluated.•EEG resting-state predicts learning but not offline consolidation.•Modulations of resting state are apparent at the alpha-band in left parietal areas.•Alpha-band resting-state provides the optimal neural resources for upcoming tasks.